Expression profiling and functional analysis reveals that TOR is a key player in regulating photosynthesis and phytohormone signaling pathways in Arabidopsis - Dong, Pan; Xiong, Fangjie; Que, Yumei; Wang, Kai; Yu, Lihua; Li, Zhengguo; Maozhi, Ren (Frontiers in Plant Science, 2015)
Target of rapamycin (TOR) acts as a master regulator to control cell growth by integrating nutrient, energy, and growth factors in all eukaryotic species. TOR plays an evolutionarily conserved role in regulating the transcription of genes associated with anabolic and catabolic processes in Arabidopsis, but little is known about the functions of TOR in photosynthesis and phytohormone signaling, which are unique features of plants. In this study, AZD8055 (AZD) was screened as the strongest active-site TOR inhibitor (asTORi) in Arabidopsis compared with TORIN1 and KU63794 (KU). Gene expression profiles were evaluated using RNA-seq after treating Arabidopsis seedlings with AZD. More than 3-fold differentially expressed genes (DEGs) were identified in AZD-treated plants relative to rapamycin-treated plants in previous studies. Most of the DEGs and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways involved in cell wall elongation, ribosome biogenesis and cell autophagy were common to both AZD- and rapamycin-treated samples, but AZD displayed much broader and more efficient inhibition of TOR compared with rapamycin. Importantly, the suppression of TOR by AZD resulted in remodeling of the expression profile of the genes associated with photosynthesis and various phytohormones, indicating that TOR plays a crucial role in modulating photosynthesis and phytohormone signaling in Arabidopsis. These newly identified DEGs expand the understanding of TOR signaling in plants. This study elucidates the novel functions of TOR in photosynthesis and phytohormone signaling and provides a platform to study the downstream targets of TOR in Arabidopsis.